EFEKTIFITAS LARVASIDA AKAR BIDURI (CALOTROPIS GIGANTEA) SEBAGAI ALTERNATIF PEMBASMI JENTIK NYAMUK AEDES AEGYPTI - Yulianti, Desi; yusmidiarti, yusmidiarti (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Biduri plants (Calatropis gigantea) is a wild plant that is very difficult to destroybecause of rapid breeding. One of the toxins contained in Biduri is saponin. Therefore Biduriplants very well be used as a repellent for Aedes aegypti mosquito larvae. The researchobjective was to determine the effectiveness of the roots Biduri larvicides against Aedesaegypti larvae mortality.This research is True Experiments with posttest study design OnlyControl Group Design. Statistical test results obtained by the one way Anova sig. = 0.000 sothat ρ <α (0.05) means that there is a significant influence on differences in dosing solutionBiduri roots are used against Aedes aegypti larvae mortality. Further post hoc test to determinedifferences in average - average each treatment group using Multiple Comparisons Analysis,LSD (Least Square Difference) obtained sig. = 0.00 so that ρ <α (0.05) means that there aresignificant differences in the deadly Aedes aegypti larvae of the four doses were given.Control of Aedes aegypti larvae using Biduri root solution can be done by affixing the rootsolution with 38 ml of solution Biduri root Biduri every 1 liter of water for 24 hours ofexposure.